At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Discover detailed solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Answer:
x=6
Step-by-step explanation:
10-5x=3(x-4)-2(x+7)
Distribute
10-5x=3x-12-2x14
Combine like terms
10-5x = x-26
add 5x to each side
10-5x+5x = x+5x-26
10 = 6x-26
Add 26 to each side
10+26 = 6x-26+26
36 = 6x
Divide by 6
36/6 = 6x/6
6 =x
Answer:
[tex]10-5x=3\left(x-4\right)-2\left(x+7\right)[/tex]
[tex]3\left(x-4\right)-2\left(x+7\right)[/tex]
combine like terms:-
[tex]=3x-12-2x-14[/tex]
[tex]3x-2x=x[/tex]
[tex]=x-12-14[/tex]
Subtract -12 -14
[tex]=x-26[/tex]
[tex]10-5x=x-26[/tex]
Subtract 10 from both sides:-
[tex]-5x=x-36[/tex]
Now, subtract x from both sides:-
[tex]-5x-x=x-36-x[/tex]
[tex]-6x=-36[/tex]
Divide both sides by -6:-
[tex]\frac{-6x}{-6}=\frac{-36}{-6}[/tex]
[tex]x=6[/tex]
OAmalOHopeO
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.